Que fait le salariat au militantisme dans les associations féministes ? - Erika Flahault; Dominique Loiseau (Amnis)
The women’s rights organizations (MFPF, SOS Femmes, CIDFF) were created in France in 1960/1970 in the context of feminist activism. Today they face paradoxical difficulties, since they partly result from their success and their sustainability. Indeed, to increase militant efficiency, to meet the still existing women’s needs which they address, they have resorted to employment and have become employers. In a context where they can only offer their employees devalued jobs because of their difficulty to ensure their economic survival, they are in contradiction with their values, without being always aware of it at first. Therefore the female employees’ arrival questions the militancy of "militant employers". But once the early times of destabilization are over, the associations are trying to react and put solutions in place allowing the two dimensions, activist and professional, to be conciliated.